Zanthoxylum Species: A Comprehensive Review of Traditional Uses, Phytochemistry, Pharmacological and Nutraceutical Applications - Innocent Uzochukwu Okagu; Joseph Chinedu Ndefo; Emmanuel Chigozie Aham; Chibuike C. Udenigwe (Molecules, 2021)
Zanthoxylum species (Syn. Fagara species) of the Rutaceae family are widely used in many countries as food and in trado-medicinal practice due to their wide geographical distribution and medicinal properties. Peer reviewed journal articles and ethnobotanical records that reported the traditional knowledge, phytoconstituents, biological activities and toxicological profiles of Z. species with a focus on metabolic and neuronal health were reviewed. It was observed that many of the plant species are used as food ingredients and in treating inflammation, pain, hypertension and brain diseases. Over 500 compounds have been isolated from Z. species, and the biological activities of both the plant extracts and their phytoconstituents, including their mechanisms of action, are discussed. The phytochemicals responsible for the biological activities of some of the species are yet to be identified. Similarly, biological activities of some isolated compounds remain unknown. Taken together, the Z. species extracts and compounds possess promising biological activities and should be further explored as potential sources of new nutraceuticals and drugs.